First record of the male of Leusaba philippina Stål (Hemiptera: Fulgoromorpha: Tropiduchidae) with a redescription of the genus and species - Wang, Rong-Rong; Webb, Michael D.; Liang, Ai-Ping (Zootaxa, 2010)
The male of Leusaba philippina Stål (Philippines) is recorded for the first time. Redescriptions of the genus and species based on the newly found male and other specimens are provided. Taxonomic notes on the remaining species of the genus, L. marginalis Walker (Borneo), L. rufitarsis (Kirby) (Sri Lanka) and two un-named species are given.